2018
DOI: 10.1016/j.idcr.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Fatal breakthrough mucormycosis in a multivisceral transplant patient receiving micafungin: Case report and literature review

Abstract: IntroductionAntifungal agents are routinely used in the post-transplant setting for both prophylaxis and treatment of presumed and proven fungal infections. Micafungin is an echinocandin-class antifungal with broad antifungal cover and favorable side effect profile but, notably, it has no activity against molds of the order Mucorales.Presentation of caseA 47-year-old woman underwent multivisceral transplantation for intestinal failure-associated liver disease. She had a prolonged post-operative recovery compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Eleven additional studies were found during the hand‐screening of the included articles’ references or the hand‐screening of the references of narrative reviews. Finally, 60 met the present study's inclusion criteria 5,6,11‐68 . The review process is graphically presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven additional studies were found during the hand‐screening of the included articles’ references or the hand‐screening of the references of narrative reviews. Finally, 60 met the present study's inclusion criteria 5,6,11‐68 . The review process is graphically presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, breakthrough mucormycosis has been reported after echinocandin prophylaxis in 10-14% of mucormycosis cases [104,105,106]. A recent study reported six cases of breakthrough mucormycosis after micafungin prophylaxis [107]. A stringent case control study is essential to investigate the association of antifungal agents in breakthrough mucormycosis and clinicians should be aware of the risk of mucormycosis in high risk populations with prior antifungal prophylaxis.…”
Section: Underlying Disease/predisposing Factorsmentioning
confidence: 99%
“…In SAH, paradoxical “immune exhaustion” and an accumulation of other predisposing factors like steroids lead to an increased risk of IFIs and sepsis 6 . It is conceivable that in our patient, colonization and possible infiltration of the surgical site may have happened during exploratory laparotomy and progressed to invasive disease due to the recipient's inappropriate net immunosuppression status and targeted antifungal prophylaxis (TAP) with broad‐spectrum echinocandin therapy 7,8 …”
Section: Figurementioning
confidence: 97%
“…The initial evaluation revealed that the patient had acute severe alcoholic hepatitis (SAH) with grade 1 acute-on-chronic liver failure 6 It is conceivable that in our patient, colonization and possible infiltration of the surgical site may have happened during exploratory laparotomy and progressed to invasive disease due to the recipient's inappropriate net immunosuppression status and targeted antifungal prophylaxis (TAP) with broad-spectrum echinocandin therapy. 7,8 This case highlights several unmet needs in the management of SAH.…”
mentioning
confidence: 89%